Glucocorticoids preserve the t-tubular system in ventricular cardiomyocytes by upregulation of autophagic flux - Seidel, Thomas; Fiegle, Dominik; Baur, Tim J.; Ritzer, Anne; Nay, Sandra; Heim, Christian; Weyand, Michael; Milting, Hendrik; Oakley, Robert H.; Cidlowski, John A.; Volk, Tilmann (Basic Research in Cardiology, 2019)
A major contributor to contractile dysfunction in heart failure is remodelling and loss of the cardiomyocyte transverse tubular system (t-system), but underlying mechanisms and signalling pathways remain elusive. It has been shown that dexamethasone promotes t-tubule development in stem cell-derived cardiomyocytes and that cardiomyocyte-specific glucocorticoid receptor (GR) knockout (GRKO) leads to heart failure. Here, we studied if the t-system is altered in GRKO hearts and if GR signalling is required for t-system preservation in adult cardiomyocytes. Confocal and 3D STED microscopy of myocardium from cardiomyocyte-specific GRKO mice revealed decreased t-system density and increased distances between ryanodine receptors (RyR) and L-type Ca2+ channels (LTCC). Because t-system remodelling and heart failure are intertwined, we investigated the underlying mechanisms in vitro. Ventricular cardiomyocytes from failing human and healthy adult rat hearts cultured in the absence of glucocorticoids (CTRL) showed distinctively lower t-system density than cells treated with dexamethasone (EC50 1.1 nM) or corticosterone. The GR antagonist mifepristone abrogated the effect of dexamethasone. Dexamethasone improved RyR–LTCC coupling and synchrony of intracellular Ca2+ release, but did not alter expression levels of t-system-associated proteins junctophilin-2 (JPH2), bridging integrator-1 (BIN1) or caveolin-3 (CAV3). Rather, dexamethasone upregulated LC3B and increased autophagic flux. The broad-spectrum protein kinase inhibitor staurosporine prevented dexamethasone-induced upregulation of autophagy and t-system preservation, and autophagy inhibitors bafilomycin A and chloroquine accelerated t-system loss. Conversely, induction of autophagy by rapamycin or amino acid starvation preserved the t-system. These findings suggest that GR signalling and autophagy are critically involved in t-system preservation and remodelling in the heart.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Autophagy; Calcium signalling; Excitation–contraction coupling; Glucocorticoid receptor; Heart failure; Remodelling; Transverse tubular system

Rapid Pacing Decreases L-type Ca2+ Current and Alters Cacna1c Isogene Expression in Primary Cultured Rat Left Ventricular Myocytes - Ritzer, Anne; Röschl, Tobias; Nay, Sandra; Rudakova, Elena; Volk, Tilmann (Journal of Membrane Biology, 2023)
The L-type calcium current (ICaL) is the first step in cardiac excitation–contraction-coupling and plays an important role in regulating contractility, but also in electrical and mechanical remodeling. Primary culture of cardiomyocytes, a widely used tool in cardiac ion channel research, is associated with substantial morphological, functional and electrical changes some of which may be prevented by electrical pacing. We therefore investigated ICaL directly after cell isolation and after 24 h of primary culture with and without regular pacing at 1 and 3 Hz in rat left ventricular myocytes. Moreover, we analyzed total mRNA expression of the pore forming subunit of the L-type Ca2+ channel (cacna1c) as well as the expression of splice variants of its exon 1 that contribute to specificity of ICaL in different tissue such as cardiac myocytes or smooth muscle. 24 h incubation without pacing decreased ICaL density by 10% only. Consistent with this decrease we observed a decrease in the expression of total cacna1c and of exon 1a, the dominant variant of cardiomyocytes, while expression of exon 1b and 1c increased. Pacing for 24 h at 1 and 3 Hz led to a substantial decrease in ICaL density by 30%, mildly slowed ICaL inactivation and shifted steady-state inactivation to more negative potentials. Total cacna1c mRNA expression was substantially decreased by pacing, as was the expression of exon 1b and 1c. Taken together, electrical silence introduces fewer alterations in ICaL density and cacna1c mRNA expression than pacing for 24 h and should therefore be the preferred approach for primary culture of cardiomyocytes. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cacna1c; Cardiac memory; Regional differences; Remodeling

Region-specific mechanisms of corticosteroid-mediated inotropy in rat cardiomyocytes - Wacker, Caroline; Dams, Niklas; Schauer, Alexander; Ritzer, Anne; Volk, Tilmann; Wagner, Michael (Scientific Reports, 2020)
Regional differences in ion channel activity in the heart control the sequence of repolarization and may contribute to differences in contraction. Corticosteroids such as aldosterone or corticosterone increase the L-type Ca2+ current (ICaL) in the heart via the mineralocorticoid receptor (MR). Here, we investigate the differential impact of corticosteroid-mediated increase in ICaL on action potentials (AP), ion currents, intracellular Ca2+ handling and contractility in endo- and epicardial myocytes of the rat left ventricle. Dexamethasone led to a similar increase in ICaL in endocardial and epicardial myocytes, while the K+ currents Ito and IK were unaffected. However, AP duration (APD) and AP-induced Ca2+ influx (QCa) significantly increased exclusively in epicardial myocytes, thus abrogating the normal differences between the groups. Dexamethasone increased Ca2+ transients, contractility and SERCA activity in both regions, the latter possibly due to a decrease in total phospholamban (PLB) and an increase PLBpThr17. These results suggest that corticosteroids are powerful modulators of ICaL, Ca2+ transients and contractility in both endo- and epicardial myocytes, while APD and QCa are increased in epicardial myocytes only. This indicates that increased ICaL and SERCA activity rather than QCa are the primary drivers of contractility by adrenocorticoids.
CRIS-Team Scopus Importer:2020-07-24

Transcriptional regulation of the L-type Ca2+ channel alpha C-1-subunit by corticosteroid - Ritzer, Anne; Rudakova, Elena; Volk, Tilmann (2017)
EVALuna2:214662